2006
DOI: 10.7863/jum.2006.25.5.593
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Sonography With Micro Convex Probes in Diagnosing Meniscal Tears Compared With Arthroscopy

Abstract: Meniscal tears are common in all age groups. The use of sonography allows rapid, low-cost, and noninvasive exploration of meniscal tears as a first-line diagnostic method. We recommend high-resolution micro convex probes, which better fit the anatomic concavity of the popliteal fossa, as efficient investigation tools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 21 publications
3
31
0
Order By: Relevance
“…In our prospective study, ultrasonography was found to be a highly sensitive and specific imaging method for both the detection and definition of meniscal tears, comparable with MRI. A recent study by Najafi et al 8 in 2006 reports a 100% and 95% sensitivity and specificity of ultrasonography in detecting meniscal tears, respectively, and high-resolution microconvex probes were recommended for making a diagnosis of meniscal tears. However, they only examined the posterior horns of both menisci, and they chose patients with positive ultrasonographic findings who had been examined arthroscopically.…”
Section: Discussionmentioning
confidence: 98%
“…In our prospective study, ultrasonography was found to be a highly sensitive and specific imaging method for both the detection and definition of meniscal tears, comparable with MRI. A recent study by Najafi et al 8 in 2006 reports a 100% and 95% sensitivity and specificity of ultrasonography in detecting meniscal tears, respectively, and high-resolution microconvex probes were recommended for making a diagnosis of meniscal tears. However, they only examined the posterior horns of both menisci, and they chose patients with positive ultrasonographic findings who had been examined arthroscopically.…”
Section: Discussionmentioning
confidence: 98%
“…Ultrasonographic imaging of the menisci may demonstrate a wide and irregularly shaped lateral discoid meniscus in type 1 and 2 discoid menisci with an overall accuracy of more than 70%. (9,11). Magnetic resonance imaging (MRI) is widely used to diagnose musculoskeletal pathologies affecting the knee.…”
Section: Introductionmentioning
confidence: 99%
“…The use of high-resolution micro convex probes, which better fit the anatomic concavity of the popliteal fossa, achieves a sensitivity of 100% and a specificity of 95% in detecting meniscal tears. The positive predictive value was reported to be 95% and 93% for the medial and lateral menisci, respectively, and the negative predictive value was 100% [39]. It is important to point out that ultrasonography (US) is an examiner-dependent tool and should be evaluated accordingly in the clinical setting.…”
Section: Ultrasonographymentioning
confidence: 99%